(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This paper examines the distributive analysis of polymodality within authentic discourse contexts. It investigates how multiple modal expressions co-occur, interact, and influence meaning across various genres. Using a combination of corpus linguistics methods and qualitative discourse analysis, the study identifies common frequency patterns, semantic functions, and pragmatic roles of polymodal constructions in English. The findings demonstrate that polymodality allows speakers and writers to negotiate stance, maintain politeness, and adjust levels of certainty with greater nuance. Overall, this research advances understanding of modality in discourse and provides practical insights for language teaching and translation.